Role of Immunomodulators in Reducing Postoperative Inflammation in Facial Reconstructive Surgery - Khan, Ihsanullah; Ishaq, Irfan; Awan, Asadullah; Hussain, Majid; Baloch, Masroor Ahmad; Saleem, Muhammad Hammad (Journal of Neonatal Surgery, 2025)
Background: Reconstructive surgery on the face routinely provokes a strong inflammatory reaction that slows wound healing and raises the likelihood of complications. Surgeons have therefore turned to immunomodulating agents to tame this response, yet the supporting clinical evidence remains sparse. This study aimed to evaluate the effectiveness of immunomodulators in reducing inflammation and improving recovery outcomes following facial reconstructive surgery. Methods: Between January 2023 and January 2024, a prospective comparative study at Burns and Plastic Surgery Center Hayatabad, enrolling 61 subjects who received facial reconstructive surgery. Participants were allocated to two cohorts: those treated with immunomodulatory medication (Group A, n=31) and a control group that received standard care alone (Group B, n=30). Investigators recorded and statistically analyzed postoperative inflammation markers, clinical signs, wound healing duration, and any post-surgical complications. Results: Patients in Group A demonstrated significantly lower CRP, WBC, and IL-6 levels within 24 hours postoperatively (p < 0.01). They also exhibited reduced facial swelling, faster wound healing, and fewer infections compared to the control group. Hospital stay was shorter in the immunomodulator group (p < 0.001). No serious adverse events were associated with immunomodulator use. Conclusion: The use of immunomodulators, particularly corticosteroids, appears to effectively reduce inflammation and support better recovery in facial reconstructive surgery. Their inclusion in perioperative management protocols may improve both clinical outcomes and patient satisfaction..